Ketidakselesaan otot skeletal dan prestasi kerja di kalangan pengguna terminal paparan video di Jabatan Audit Negara, Cawangan Sarawak - Toieyah, Binti Tioh (Universiti Malaysia Sarawak (UNIMAS), 2002)
This study is aimed at determining musculoskeletal discomfort and work performance among video display terminal (VDT) users at the National Audit Office, Sarawak Branch. Subjectʼs work performance was measured on the basis of the quality of the documents generated